SURGICAL OUTCOMES OF SINGLE-LEVEL CERVICAL ARTIFICIAL DISC REPLACEMENT FOR THE TREATMENT OF CERVICAL DISC HERNIATION AT VIET DUC FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with single-level cervical disc herniation and to evaluate the surgical outcomes of cervical artificial disc replacement (CDR) in this population.Subjects and methods: A retrospective descriptive study was conducted on 47 patients with single-level cervical disc herniation who underwent surgical treatment and follow-up at Viet Duc University Hospital from 2020 to 2025.Results: The mean patient age was 45.1 ± 8.34 years, with a predominance of females (78.7%). Clinically, cervical radiculopathy was the most frequent manifestation (66%). MRI findings showed that central – paracentral herniation was the most common pattern (59.6%), predominantly at the C5–6 level (61.7%). Surgical outcomes demonstrated significant improvements: neck VAS decreased from 5.27 preoperatively to 0.92 at 5-year follow-up, and arm VAS from 5 to 0.5. NDI improved from moderate–complete disability preoperatively (93.6%) to no – mild disability (100%) at 3 – 5 years postoperatively. JOA scores increased from 14.68 ± 1.3 before surgery to 16.8 ± 0.39 at 5 years. Total cervical range of motion improved from 44.3° to 58.1°, while functional spinal unit motion increased from 12.49° to 18.8°. The postoperative complication rate was 8.4%, including superficial infection (4.2%) and transient dysphagia (4.2%).Conclusion: CDR provides sustained therapeutic benefits for single-level cervical disc herniation, offering significant pain reduction, functional improvement, preservation of cervical mobility, and a low rate of postoperative complications.
Keywords: Cervical disc herniation, cervical artificial disc replacement.